Effect of Atogepant for Preventive Migraine Treatment on Patient-Reported Outcomes in the Randomized, Double-blind, Phase 3 ADVANCE Trial. (21st February 2023) - Lipton, Richard B.; Pozo-Rosich, Patricia; Blumenfeld, Andrew M.; Li, Ye; Severt, Lawrence; Stokes, Jonathan T.; Creutz, Lela; Gandhi, Pranav; Dodick, David
Abstract : Background and Objectives: The oral calcitonin gene–related peptide receptor antagonist atogepant is indicated for the preventive treatment of episodic migraine. We evaluated changes in patient-reported outcomes with atogepant in adults with migraine. Methods: In this phase 3, 12-week, multicenter, randomized, double-blind, placebo-controlled, parallel-group trial (ADVANCE), adults with 4–14 migraine days per month received atogepant (10, 30, or 60 mg) once daily or placebo. Secondary endpoints included changes from baseline in Migraine-Specific Quality-of-Life Questionnaire (MSQ) version 2.1 Role Function–Restrictive (RFR) domain at week 12 and mean monthly Activity Impairment in Migraine–Diary (AIM-D) Performance of Daily Activities (PDA) and Physical Impairment (PI) domains across the 12-week treatment period. Exploratory endpoints included change in MSQ Role Function–Preventive (RFP) and Emotional Function (EF) domains; AIM-D total scores; and change in Headache Impact Test (HIT)–6 scores. Results: Of 910 participants randomized, 873 comprised the modified intent-to-treat population (atogepant: 10 mg [n = 214]; 30 mg [n = 223]; and 60 mg [n = 222]; placebo [n = 214]). All atogepant groups demonstrated significantly greater improvements vs placebo in MSQ RFR that exceeded minimum clinically meaningful between-group difference (3.2 points) at week 12 (least-square mean difference [LSMD] vs placebo: 10 mg [9.9]; 30 mg [10.1]; 60 mg [10.8]; all p < 0.0001). LSMDs in monthly AIM-D PDA and PI scores across the 12-week treatment period improved significantly for the atogepant 30 (PDA: −2.54; p = 0.0003; PI: −1.99; and p = 0.0011) and 60 mg groups (PDA: −3.32; p < 0.0001; PI: −2.46; p < 0.0001), but not for the 10 mg group (PDA: −1.19; p = 0.086; PI: −1.08; p = 0.074). In exploratory analyses, atogepant 30 and 60 mg were associated with nominal improvements in MSQ RFP and EF domains, other AIM-D outcomes, and HIT-6 scores at the earliest time point (week 4) and throughout the 12-week treatment period. Results varied for atogepant 10 mg. Discussion: Atogepant 30 and 60 mg produced significant improvements in key patient-reported outcomes including MSQ-RFR scores and both AIM-D domains. Nominal improvements also occurred for other MSQ domains and HIT-6, reinforcing the beneficial effects of atogepant as a new treatment for migraine prevention. Trial Registration Information: ClinicalTrials.gov NCT03777059. Submitted: December 13, 2018; First patient enrolled: December 14, 2018. clinicaltrials.gov/ct2/show/NCT03777059 . Classification of Evidence: This study provides Class II evidence that daily atogepant is associated with improvements in health-related quality-of-life measures in patients with 4–14 migraine days per month.